Promotion of Pupils ’ Emotional Development in the Process of Listening to Music in Music Classes in Elementary School - Mūrniece, Laima; Zakovska, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Emotionality or person’s ability to feel something keenly and sense is an important component of person’s development to which a serious attention should be paid in the educational process. Pupils’ spiritual world is enriched by situations in the learning tasks which are perceived through emotions, empathy, feelings of happiness and satisfaction. The aim of the article is to study the possibilities to promote development of pupils’ emotionality in the process of listening to music in music classes in elementary school. Research methods – analysis of scientific literature, pedagogical observation, survey. The research justifies the close contiguity between listening to the music and music perception, which, based on the pupils’ obtained musical experience, provides for formation of emotional experience of the image of composition and evaluating skills.